The Synchronous Network of small Robotic Telescopes (Ukrainian RoboNet. Avant-project) - Zhilyaev, B.E.; Svyatogorov, O.A.; Tarady, V.K.; Sergeev, A.V.; Karpov, N.V. (Известия Крымской астрофизической обсерватории, 2007)
The Synchronous Network of small Robotic Telescopes (Ukrainian RoboNet. Avant-project)